Ammonium vanadate/ammonia precipitation for vanadium production from a high vanadate to sodium ratio solution obtained via membrane electrolysis method. (1st August 2020) - Pan, Bo; Liu, Biao; Wang, Shaona; Wenzel, Marco; Weigand, Jan J.; Feng, Man; Du, Hao; Zhang, Yi
Abstract: Vanadium is an important strategic metal and has been widely applied in a multiple of industries. However, the current process for the production of vanadium compounds suffers from the generation of a significant amount of high salinity ammonium containing wastewater due to the mixing of sodium salts, ammonium salts, and acid during vanadium precipitation operation. In order to avoid the generation of wastewater at source, a clean and recyclable V2 O5 production process was proposed and investigated in this study. Using NH4 VO3 and NH3 ·H2 O as precipitants, (NH3 )2 ·3V2 O5 ·H2 O and (NH3 )2 ·V2 O5 ·H2 O were obtained by precipitation of vanadate (Vx Oy n− ) from a high vanadate to sodium (V/Na) molar ratio acidic solution obtained via membrane electrolysis method, avoiding the generation of wastewater or solid waste. After calcination, high purity V2 O5 product could be obtained. The vanadium precipitation process was investigated using ICP, XPS, SEM, XRD techniques, and the precipitation rate was investigated using solution conductivity method. Critical precipitation parameters such as excessive coefficient, solution temperature, solution V/Na molar ratio and solution pH were examined in detail. The results showed that increase the excessive coefficient, solution temperature and solution V/Na molar ratio, as well as reduce the solution pH would be beneficial for obtaining high purity vanadium products (≥99.9% V2 O5 ). Optimum parameters were obtained at the V/Na molar ratio of 2.58, the excessive coefficient of 2, and the solution temperature of 363 K. The vanadium products obtained using both precipitants have a similar purity (more than 99.9%), however, due to a higher degree of hydrolysis reaction, the NH4 VO3 precipitation method showed a higher Vx Oy n− precipitation rate (66.36%) in comparison with the NH3 ·H2 O precipitation method (38.76%), indicating that the first method was superior. Based on this, a complete process with zero waste emission for V2 O5 production was designed. The methods proposed and the results obtained from this study could provide fundamental information for the design of cleaner vanadium production process. Graphical abstract: Image 1 Highlights: Membrane electrolysis method was proven to be effective for the separation of Vx Oy n− and Na + in NaVO3 solutions. NH4 VO3 and NH3 ·H2 O were used as precipitants, avoiding the generation of waste water or solid waste. The solution V/Na molar ratio before precipitation has significant effects on the Vx Oy n− precipitation process. Recyclable Vx Oy n− precipitation processes were designed, realizing the cleaner production of vanadium products.